Waterfowl Kill by Cree Hunters of the Hudson Bay Lowland, Ontario - Prevett, J.P.; Lumsden, H.G.; Johnson, F.C. (ARCTIC, 1983)
From 1974 to 1976 annual interviews were conducted with 97% of male Indian potential hunters at James Bay and Hudson Bay coastal villages to determine waterfowl kill. Sample interviews were conducted at inland villages. Of those interviewed at coastal communities, 87% hunted waterfowl. The mean yearly take of all species ranged from 55 to 145 birds per hunter. Lesser Snow Geese and large Canada Geese were the main prey, averaging 38,350 and 23,152 birds shot per year, respectively. Small numbers of other goose species were taken. The duck kill averaged 22,715. Eighty percent of the large Canada Goose kill occurred in spring; 76% of Snow Geese were taken in fall. Considerable inter-year variation in total kill occurred. The take for the highest kill year (1975-76) exceeded that for the lowest (1976-77) by 61% for Snow Geese and 34% for large Canada Geese; the spring kill was particularly variable. The kill of Snow Geese has apparently increased by a factor of 2, and that of large Canada Geese by a factor of 3, since the mid-1950s. Through analysis of band recoveries, the kill was determined to have been apportioned among separately managed stocks. The Indian kill made up approximately 13% of the total hunting kill of the Tennessee Valley Population, 9% of the Mississippi Valley Population, and 7% of Hudson Bay Lesser Snow Geese.Key words: Indian wildlife kill, waterfowl harvest, Hudson Bay Lowland, Cree De 1974 à 1976, nous avons interviewé chaque année 97% des chasseurs indiens males possibles dans les villages côtiers de la baie d'Hudson et de la baie James, en Ontario, ainsi que dans villages intérieurs servant d'échantillons, afin de déterminer le nombre d'oiseaux marins tués. Quatre-vingt-sept pour cent des hommes interviewés dans les communautés côtières faisaient la chasse aux oiseaux marins. Le nombre annuel moyen de proies comptant toutes les espèces variait entre 55 et 145 oiseaux par chasseur dans divers villages. Les oies blanches de taille inférieure et les bernaches canadiennes de grosse taille ...